The South African income tax implications of transactions entered into to earn points for a Broad- Based Black Economic Empowerment scorecard, with reference to a selection of structures - Jaga, Praksha (Rhodes University, Faculty of Commerce, Department of Accounting)
This thesis discussed the South African income tax implications, in terms of the Income Tax Act, No. 58 of 1962, arising from complying with Broad-Based Black Economic Empowerment requirements, and related principles established in case law. Various structures and transactions entered into for the purposes of earning points for the B-BBEE scorecard were identified. In the assessment of the deductibility of B-BBEE expenditure in terms of the preamble to section 11, section 11(a) and section 23(g) of the Act, it was highlighted that, in the South African economic environment, B-BBEE compliance represents a competitive advantage for entities. In addition, many South African organisations are required to comply with B-BBEE requirements for legal and regulatory purposes. The analysis of the deductibility of B-BBEE expenditure revealed that taxpayers that incur this expenditure would be carrying on a trade or commencing to do so. It was also concluded that B-BBEE expenditure is incurred in the production of income and would generally not be capital in nature, except in certain circumstances, in which case the Act provides certain allowances. Any deduction will only be allowed in the year of assessment in which the expenditure is actually incurred, or when the taxpayer incurs an unconditional legal obligation. This thesis explored several alternatives to achieve the requirements of the ownership element of B-BBEE and highlighted the income tax implications that arise because of these structures. It was also observed that there are a number of incentives in the Act that could be beneficial to taxpayers seeking to earn points for the remaining elements of the B-BBEE scorecard. A legal interpretive approach, in particular a doctrinal research methodology, was adopted in carrying out this research. This research concluded that the Act facilitates most of the B-BBEE transactions and structures, but due to the complex and sometimes uncertain nature of the tax consequences of B-BBEE transactions and structures, there is a need for further guidance in this area of tax law.
Keywords: Black Economic Empowerment (Program : -- South Africa); South Africa. Income Tax Act, 1962; Income tax -- Law and legislation -- South Africa; Spendings tax -- South Africa; Tax deductions -- South Africa